Selection of Fructophilic Yeast from Sun-Dried Pedro Ximénez Grape Must for the Development of New Vinegars Containing Gluconic Acid - Juan Carbonero-Pacheco; Álvaro García-Jiménez; Juan C. Mauricio; Juan C. García-García; Juan J. Román-Camacho; Elena García-Muñoz; Inés M. Santos-Dueñas; Teresa García-Martínez; Isidoro García-García (Foods, 2025)
Wine vinegar and wine are traditional Spanish products, obtained from grape must by alcoholic fermentation (wine) and subsequent acetification (vinegar). Although these are established products, there is great interest in the development of new products, particularly new vinegars, and among these, the possibility of vinegars containing gluconic acid stands out. Gluconic acid in vinegar, mainly produced by acetic acid bacteria (AAB), is positively valued by consumers. Its content depends on the availability of glucose in the base wine; however, this hexose is preferentially consumed by the indigenous yeast population which conducts the previous alcoholic fermentation. For this reason, the use of non-conventional fructophilic yeasts, which consume fructose rather than glucose, is required. In this work, we isolated, screened, and identified osmophilic and fructophilic non-Saccharomyces yeasts from sun-dried grape must and tested them under different fermentation conditions in synthetic and natural grape musts, in order to obtain a base wine with ethanol and glucose content for the development of new vinegars containing gluconic acid. The isolate of the species Starmerella lactis-condensi was found to be an ideal candidate due to its fructophilic and osmophilic features, which allowed for the production of a base wine with high ethanol (11% v/v) and glucose (up to 200 g/L) content from a natural concentrated must. In fresh must, inoculation with Starmerella lactis-condensi resulted in faster and preferential fructose consumption over glucose compared to the control. However, both sugars were completely consumed at the end of the alcoholic fermentation; therefore, new fermentation strategies should be tested in this type of must. Furthermore, this strain could be of interest in oenology due to its high glycerol yield and low volatile acid production during alcoholic fermentation. The use of this strain could allow for the production of new wines with unique metabolic profiles suitable for further vinegar production.